2018
DOI: 10.3389/fchem.2018.00251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exogenous General Plant Growth Regulators on the Growth of the Duckweed Lemna minor

Abstract: Gibberellic acid (GA3), indole-3-acetic acid (IAA), salicylic acid (SA), abscidic acid (ABA), jasmonic acid (JA) 1-amino cyclopropane-1-carboxylic acid (ACC) and aminoethoxyvinylglycine (AVG) are popular growth regulators of plants. However, the effects of their exogenous addition on the biomass production of aquatic plants, including Lemnoideae plants, “duckweeds,” are largely unknown. In this study, the growth of Lemna minor was tested for 10 d in Hoagland medium containing each compound at different concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 40 publications
2
18
0
1
Order By: Relevance
“…Among the common PGPB evaluation criteria tested in this study, there was no correlation between the strength of the PGP effect and the number or type of the observed PGP traits: F-183 showed only IAA production, TBR-22 showed nothing positive, and P23 exhibited phosphate solubilization solely. We found that external addition of IAA did not improve the growth of L. aequinoctialis ( Figure S5 , consistent with a previous report describing a negligible effect of IAA on the growth of L. minor [ 64 ]), suggesting that IAA production did not contribute to the PGP ability of the F-183 strain. On the other hand, it was reported that 79% of endophytic bacterial isolates from Landoltia , Lemna , Spirodela , and Wolffia were positive in the Salkowski reagent assay [ 65 ].…”
Section: Discussionsupporting
confidence: 91%
“…Among the common PGPB evaluation criteria tested in this study, there was no correlation between the strength of the PGP effect and the number or type of the observed PGP traits: F-183 showed only IAA production, TBR-22 showed nothing positive, and P23 exhibited phosphate solubilization solely. We found that external addition of IAA did not improve the growth of L. aequinoctialis ( Figure S5 , consistent with a previous report describing a negligible effect of IAA on the growth of L. minor [ 64 ]), suggesting that IAA production did not contribute to the PGP ability of the F-183 strain. On the other hand, it was reported that 79% of endophytic bacterial isolates from Landoltia , Lemna , Spirodela , and Wolffia were positive in the Salkowski reagent assay [ 65 ].…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary, all seven bacterial strains positively affected the multiplication rates of the duckweed specimens (the sole exception is the K. oxytoca strain 14 in the medium with 500 mg L −1 of phenol). The strains used in this study are probably not IAA producers; however, the limitation of Salkowski essay applied in this study implied that tested strains might still have produced a low-level of IAA sufficient to affect the growth of duckweed [29,47]. The interactions of IAA-producing bacteria and aquatic plants are further complicated by the fact that it only recently emerged that exogenous IAA probably affects the growth of aquatic plants, Lemnaceae included, in a completely opposite way to the terrestrial plants that were used as a model in the majority of PGP studies [47].…”
Section: Discussionmentioning
confidence: 95%
“…Following the observation that bacterial presence increased the multiplication rates of duckweed plants, all bacterial strains were tested for the production of IAA in the liquid MS medium in accordance with Gordon and Weber (1951), with some modifications [29,47], to test whether bacterial IAA might be the cause of this increase. Bacterial cultures were grown for 5 days under non-shaking conditions in 100 mL of the MS medium.…”
Section: Salkowski Reagent Test For the Colorimetric Indol-3-acetic Amentioning
confidence: 99%
“…Transcription factor WRKY32 has increased expression in the transition from meristem to green frond-like cell types, where it has been previously shown to be involved in ethylene signaling in tomato, where RNAi repression leads to yellowing of fruits (Zhao et al, 2021). It has been shown previously that related L. minor clones show reduced growth from exogenous ethylene treatment (Utami et al, 2018). Conversely, WRKY transcription factors associated with root cell transition are WRKY6 and WRKY65 .…”
Section: Resultsmentioning
confidence: 91%